Physical Activity Targeted at Maximal Lipid Oxidation: A Meta-Analysis - A. J. Romain; M. Carayol; M. Desplan; C. Fedou; G. Ninot; J. Mercier; A. Avignon; J. F. Brun (Journal of Nutrition and Metabolism)
Exercise is recognized as a part of the management of obesity and diabetes. Various protocols of exercise are proposed for the management of obesity, diabetes, and other metabolic diseases. One of the strategies proposed by several authors is low intensity endurance training targeted at the level of maximal oxidation. Large series using this technique are lacking. Addressing this issue, we performed a meta-analysis of the studies on anthropometric measurements. From a database of 433 articles, 15 were selected, including 279 subjects with 6 different populations. Studies duration ranged from 2 months to 12 months. Concerning weight loss, in the intervention versus control analysis, five studies with 185 participants were included with a significant effect size favors exercise (P=0.02) without significant heterogeneity (I2=0.0%, P=0.83). Further randomized controlled trials for comparing it with other exercise protocols and defining its dose effectiveness on large samples are needed.